2021
DOI: 10.3390/cancers13112560
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of IRS-4 in the Origin of Multifocal Hepatocellular Carcinoma

Abstract: New evidence suggests that insulin receptor substrate 4 (IRS-4) may play an important role in the promotion of tumoral growth. In this investigation, we have evaluated the role of IRS-4 in a pilot study performed on patients with liver cancer. We used immunohistochemistry to examine IRS-4 expression in biopsies of tumoral tissue from a cohort of 31 patient suffering of hepatocellular carcinoma (HCC). We simultaneously analyzed the expression of the cancer biomarkers PCNA, Ki-67, and pH3 in the same tissue samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Previous research has demonstrated that the stable transfection of pcDNA (IRS-4) increased IRS-4 protein levels in HepG2 cells (C1 line) in comparison to a control group (pcDNA empty vector) [ 26 ]. In Figure 5 A, we show the levels of IRS-4 mRNA in both C1 and control cells (pcDNA).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that the stable transfection of pcDNA (IRS-4) increased IRS-4 protein levels in HepG2 cells (C1 line) in comparison to a control group (pcDNA empty vector) [ 26 ]. In Figure 5 A, we show the levels of IRS-4 mRNA in both C1 and control cells (pcDNA).…”
Section: Resultsmentioning
confidence: 99%
“…Stable transfectants were obtained after selection with G418 for different periods of time. Several colonies overexpressing IRS-4 were obtained [ 26 ]. For further studies, the colony C1 was selected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin receptor substrate 4 (IRS-4) is a relevant molecule altered in different types of malignancies like BC. It seems that this molecule promotes tumoral proliferation and therapy resistance due to the alteration of different molecular pathways [13][14][15]. Furthermore, previous studies have found that an overexpression of this component is frequently related to a poorer prognosis [16].…”
Section: Introductionmentioning
confidence: 99%
“…La expresión de IRS4 presenta un patrón más restringido encontrándose principalmente en cerebro, riñones, timo e hígado. En hígado, la expresión de Irs4 aumenta junto con la de Irs2 durante la regeneración hepática [52] y se ha visto involucrado con la progresión del carcinoma hepatocelular (HCC) [53]. El ratón con deleción de Irs4 (Irs4-/-) presenta únicamente un retraso moderado del crecimiento y una intolerancia leve a la glucosa [54].…”
Section: Sustratos Del Receptor De Insulina (Irss)unclassified